Feedback bei internationalen Videokonferenzen in der Lehrendenbildung - Hoffmann, Sabine (Kritik. Rivista di letteratura e critica culturale, 2023)
The article deals with interactional processes in video conferences that took place as part of an international training and further education event for DaF-teachers. The focus is on showing how the teachers request feedback from each other in relation to the topics to be discussed and in what form they receive it. Furthermore, the role of moderation should also be examined. The aim of the study is to reveal interaction patterns that characterize the behavior of teachers in the context of digital education in order to promote a professional feedback culture when dealing with lesson observation.